1973
DOI: 10.1530/acta.0.0730771
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Conversion of [4-14c] Dehydroepiandrosterone and Androstenedione to Oestrogens by the Microsomes of Placentas From Normal, Toxaemic, Diabetic and Postmature Pregnancies

Abstract: The placental oestrogen precursors [4-14C]dehydroepiandrosterone (DHA) and [4-14C]androstenedione (AD) were incubated with microsomal fractions of human placentas from normal and pathological pregnancies at different stages of gestation, in order to evaluate the rate of conversion of the substrates to oestrogens. In placentas from normal pregnancies the capability to convert C19-steroids (DHA and AD) to C18-steroids (oestrone and oestradiol017β) increased with the age of gestation. The placenta at term metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1973
1973
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…I, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Q J 4 -androstendione was incubated with microsomal fraction (equivalent to 0.5 g fresh weight) from 12 placentones of 8 placentas. Each incubation took place with a subcellular fraction from the center and then from the periphery of the placentones, so that a direct comparison was possible in each placenta.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…I, (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Q J 4 -androstendione was incubated with microsomal fraction (equivalent to 0.5 g fresh weight) from 12 placentones of 8 placentas. Each incubation took place with a subcellular fraction from the center and then from the periphery of the placentones, so that a direct comparison was possible in each placenta.…”
Section: Resultsmentioning
confidence: 99%
“…Tissue was then homogenized in 0.25 M sucrose in a glass homogenisator. (The method has been described elsewhere [5].) Remains of connective tissue which coüld not be homogenized were * Investigations were supported by the Forschungsgemeinschaft".…”
Section: Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…The DHEA-S induced increase in urinary or plasma estrogens provides Information about the reservecapacity of the placenta. Using incubation studies with placental tissue we could demonstrate in vitro that the conversion of DHEA to estrogens by the placental aromatising enzyme-system is significantly reduced in pathological pregnancies (preeclampsia, diabetes, postmaturity) s compared to normal pregnancies [10,12,13]. These studies demonstrated that in complicated pregnancies the diminished capacity of the aromatizing enzymesystem can occur and may result in a reduced estrogen production which is of great clinical importance.…”
mentioning
confidence: 99%